2019
DOI: 10.3390/w11030442
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Enhanced Ultrafiltration Conditions for Cd with Mixed Biosurfactants Using the Box-Behnken Response Surface Methodology

Abstract: A mixture of the environmentally friendly biosurfactants rhamnolipids and sophorolipids was used as a source of micelles in this study. The Box-Behnken design and response surface methodology was used to investigate the influence of factors on micellar-enhanced ultrafiltration (MEUF). Simulated Cd-containing wastewater was used for testing. Based on single-factor experiments, the initial Cd2+ concentration, biosurfactant mixing ratio (α) and pH were chosen as influential variables, and both the Cd2+ rejection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…BBD are extensively used for second-order models in absolutesplit-plot experiments,randomized experiments and in robustfactor design settings [46]. It requires three levels for each processing factor, and experimental runs are executed depending on the combination of the factors [47].…”
Section: Box Behnken Design (Bbd)mentioning
confidence: 99%
“…BBD are extensively used for second-order models in absolutesplit-plot experiments,randomized experiments and in robustfactor design settings [46]. It requires three levels for each processing factor, and experimental runs are executed depending on the combination of the factors [47].…”
Section: Box Behnken Design (Bbd)mentioning
confidence: 99%
“…Inactivation of viral lipid envelopes and capsid [10] Anti-adhesive agents Sophorolipids Biosurfactants adsorption to a substratum modifies the surface hydrophobicity thereby interfering with microbial adhesion and desorption process Modification of the rheological characteristics of the food to a desired consistency and texture using emulsification properties [17,179,209] [175]…”
Section: Sophorolipidsmentioning
confidence: 99%
“…A vast repertoire of biosurfactants have been reported with myriad of biomolecule contents and have the highest application food and allied industries (Markande & Nerurkar, 2019). Nutrient parameters influencing the production of biosurfactants having industrial applications especially in petroleum and environmental have been consistently reported (Chai et al, 2019;Hema et al, 2019;Sharma & Pandey, 2020;Somoza-Coutiño et al, 2020;Yaraguppi, et al, 2020). But the microbial amyloid bioemulsifiers have high applicability potential in food industry as they can be stable and can be extensively resistant to sterilization conditions.…”
Section: Introductionmentioning
confidence: 99%